Diptera-VR: A Gamified Virtual Entomology Lab for Science Education - Gois, João Paulo; Russo, Vinícius T.; Carreiro, Julian V. A.; Santos, Daubian; Santos, Charles Morphy D. (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2025: Anais do XXIV Simpósio Brasileiro de Jogos e Entretenimento DigitalDO - 10.5753/sbgames.2025.9583, 2025)
Introduction: Games and Virtual Reality (VR) have proven to be powerful tools for science education, enabling immersive experiences that enhance practical learning. However, gamified virtual laboratories remain underexplored in entomology education, thereby limiting engagement and accessibility to scientific knowledge. Objective: To present Diptera-VR, a gamified Virtual Reality experience designed to simulate the environment and activities of an entomology laboratory at the Universidade Federal do ABC (UFABC), Brazil. The experience promotes science education and outreach through an interactive and immersive approach. Methodology: Diptera-VR was developed using 3D modeling and VR interaction techniques to create an engaging educational environment. Players can manipulate laboratory equipment, examine insect specimens, and perform tasks such as inspecting wings under a microscope, analyzing fossil material, and observing pinned specimens. The development process included the creation of digital assets and interaction design to ensure an accessible educational experience. Results: Diptera-VR is expected to bridge the gap between theoretical learning and scientific practice, increasing student engagement and improving knowledge retention. Additionally, it may contribute to the popularization of science in a context marked by a global environmental crisis and growing scientific denialism.